Cardiac Biomarkers Predicting MACE in Patients Undergoing Noncardiac Surgery: A Meta-Analysis - Zhang, Li-Jun; Li, Na; Li, Yang; Zeng, Xian-Tao; Liu, Mei-Yan (Frontiers in Physiology, 2019)
Abstract Objective: The present meta-analysis was aimed to systematically evaluate the effectiveness and accuracy of brain natriuretic peptide (BNP), cardiac troponin (cTn), high sensitive C reactive protein (hs-CRP) and CRP for predicting postoperative major adverse cardiovascular events (MACE) in patients undergoing noncardiac surgery. Methods: A total of 26 relevant studies with 7877 participants were collected from five databases, namely PubMed, Embase, China National Knowledge Infrastructure (CNKI), CQVIP and the Wanfang Database until August 10, 2018. And the Review Manager Version 5.3 and Stata/SE 12 software were used for data syntheses in the meta-analysis. Results: Strong relationships of BNP/NT-proBNP, cTnI/cTnT and hs-CRP with MACE were detected in patients undergoing noncardiac surgery, and the five biomarkers all increased the risk of MACE. Compared to normal levels, elevated BNP/NT-proBNP could increase the MACE risk by almost 4-fold [RR:3.92, 95%CI: 3.23-4.75, P<0.001]; elevated BNP corresponded to a 4.5-fold risk [RR:4.57, 95%CI: 3.37-6.20, P<0.001]; elevated NT-proBNP led to a 3-fold higher risk [RR:3.48, 95%CI: 2.71-4.46, P<0.001]. Comparing with normal levels of cTnI/cTnT, increased cTnI/cTnT was associated with nearly 5-fold more higher risk of MACE [RR:5.52, 95%CI: 4.62-6.58, P<0.001]; elevated cTnI faced a 5-fold risk [RR:5.21, 95%CI: 3.96-6.86, P<0.001]; elevated cTnT resulted in nearly 6-fold higher risk [RR:5.73, 95%CI: 4.55-7.22, P<0.001]. The elevation of hs-CRP was associated with nearly 4-fold higher risk of MACE in comparison with normal concentration [RR:3.73, 95%CI: 2.63-5.30, P<0.001]. Conclusion: According to the results of our meta-analysis, the elevations of BNP/NT-proBNP, cTnI/cTnT and hs-CRP, pre-operation or post-operation immediately, can predict much higher risk of postoperative MACE in patients undergoing noncardiac surgery.